A comparative study of chemical composition of Morchella esculenta (L.) Pers. from Portugal and Serbia - Heleno, Sandrina A. (2013)
Mushrooms contain a huge diversity of biomolecules with bioactive properties that should be explored. Morchella esculenta (L.) Pers. (morel) is one of the most highly prized edible mushrooms in the world. In the present work a comparative study on the chemical composition (nutritional value, primary and secondary metabolites) of the two samples from two countries, Portugal (SP) and Serbia (SS), was performed. Carbohydrates were the most abundant macronutrients, followed by proteins and ash. Fat contents were low and similar in both samples. The energetic contribution of SS was slightly higher due to the higher contribution of carbohydrates. Regarding the sugars, mannitol and trehalose were found in both samples, but fructose was only found in SP. Polyunsaturated fatty acids predominated over monounsaturated and saturated fatty acids. Linoleic, oleic and palmitic acids were abundant in both samples, but only SS gave considerable amounts of α- linolenic acid. Concerning the tocopherols, the α-, γ- and δ-tocopherols were also quantified in both samples; - and -tocopherols were observed in higher levels in SS. Oxalic and fumaric acids were in both samples; malic acid was found in SP, while quinic and citric acids were observed in SS. Finally, protocatechuic and phydroxybenzoic acids were found in both samples, but p-coumaric acid was quantified in SP. As far as we know, this is the first study reporting the chemical composition of morel samples from Portugal and Serbia.